2017
DOI: 10.1016/j.anorl.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The keys to conservative treatment of early-stage squamous cell carcinoma of the tonsillar region

Abstract: To analyze the medical literature devoted to work-up, epidemiology, local control, survival, complications and sequelae after conservative treatment for early-stage squamous cell carcinoma of the tonsillar region. An analysis of the PubMed (1975-2016) database was performed using the following keywords and associations: "tonsil/tonsillar region/oropharynx" AND "squamous cell carcinoma" AND "early-stage (I-II; T1-2N0M0)" AND "radiation therapy/radiotherapy" OR "conservative surgery/oropharyngectomy/transoral su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Despite increased serum exosomal miR‐210 expression was previously reported in glioma and renal cancer patients 13,22 raising doubts on its specificity for OSCC diagnosis, our and previous findings 12 demonstrate that miR‐210 act as an oncomiR in OSCC and its expression is not affected by age, gender, or relevant pathological variables such as TNM classification, further reinforcing the concept that EV‐miR‐210 secretion is indeed strictly related to the presence of the OSCC per se . From a clinical point of view, the early detection of OSCC offers several advantages: firstly, it allows to perform a conservative organ function surgery improving the quality of life of the patient after cancer removal 23 ; secondly, the early diagnosis could identify these tumors before they spread in the lymph node or invade surrounding tissue 24 . Finally, it has been shown that the removal of OSCC in an early stage prolongs the survival rate of these patients 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increased serum exosomal miR‐210 expression was previously reported in glioma and renal cancer patients 13,22 raising doubts on its specificity for OSCC diagnosis, our and previous findings 12 demonstrate that miR‐210 act as an oncomiR in OSCC and its expression is not affected by age, gender, or relevant pathological variables such as TNM classification, further reinforcing the concept that EV‐miR‐210 secretion is indeed strictly related to the presence of the OSCC per se . From a clinical point of view, the early detection of OSCC offers several advantages: firstly, it allows to perform a conservative organ function surgery improving the quality of life of the patient after cancer removal 23 ; secondly, the early diagnosis could identify these tumors before they spread in the lymph node or invade surrounding tissue 24 . Finally, it has been shown that the removal of OSCC in an early stage prolongs the survival rate of these patients 25…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, the early detection of OSCC offers several advantages: firstly, it allows to perform a conservative organ function surgery improving the quality of life of the patient after cancer removal 23 ; secondly, the early diagnosis could identify these tumors before they spread in the lymph node or invade surrounding tissue. 24 Finally, it has been shown that the removal of OSCC in an early stage prolongs the survival rate of these patients. 25 Some previous studies demonstrated that a number of oncogenic miRNAs are increased in EVs from OSCC patients: miR-21…”
Section: Discussionmentioning
confidence: 99%
“…This might be considered as a local recruitment bias. It could also be related to the extension of the extrinsic tongue muscles (especially the styloglossus and the palatoglossus muscles) which are difficult to assess both in terms of imaging and anatomopathology [27,28]. It is noteworthy that this stage has been recently excluded from the TNM classification.…”
Section: Limitations Of the Studymentioning
confidence: 99%